Warmer temperatures reduce chemical tolerance in the redlegged earth mite (Halotydeus destructor), an invasive winter‐active pest. Issue 7 (29th April 2022) - Thia, Joshua A; Cheng, Xuan; Maino, James; Umina, Paul A; Hoffmann, Ary A
Abstract: BACKGROUND: Quantifying how chemical tolerance of pest arthropods varies with temperature is important for understanding the outcomes of chemical control, for measuring and monitoring resistance, and for predicting how pesticide resistance will evolve under future climate change. We studied the redlegged earth mite, Halotydeus destructor (Tucker), a winter‐active invasive agricultural pest in Australia. Using a replicated block experiment, we tested the effect of different thermal conditions on the expression of chemical tolerance to a pyrethroid and two organophosphates. Our chemical bioassays were conducted on two redlegged earth mite populations: one possessed organophosphate resistance, whilst the other was susceptible to pesticides. Mites were first acclimated at cool (4 °C) and warm (14 °C) conditions and then exposed to pesticides in both cool (11 °C) and warm (18 °C) test conditions. RESULTS: Warm test conditions generally reduced chemical tolerance to all pesticides relative to cool test conditions. Median lethal dose (LD50 ) values of mites tested under cool conditions were 1.12–3.57‐fold greater than of mites tested under warm conditions. Acclimation had a variable and small impact on chemical responses. Thermal factors (ratio between test temperatures) were similar between populations for each active ingredient. Despite reduced chemical tolerances under warm test conditions for individual mite populations, resistance factors (ratio between resistant and susceptible mite populations) were relatively consistent. CONCLUSION: Our data provides context for prior theoretical work demonstrating climatically constrained pesticide resistances in Australian redlegged earth mites. Estimates of temperature dependent toxicity measured in this study may be useful in parameterizing models of redlegged earth mite control under an increasingly warm and more variable climate. © 2022 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Chemical tolerance is reduced by warm pesticide exposure temperatures in the redlegged earth mite, an invasive winter pest of Australian agriculture. Thermal variation in chemical tolerances may explain theoretically estimated limits on the evolution and spread of pesticide resistance in this pest.